Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Menengah Pertama Berdasarkan Polya - Firda, Nadiatun; Suryadi, Didi; Dahlan, Jarnawi Afgani (Edumatica : Jurnal Pendidikan Matematika, 2023)
Mathematical problem-solving ability is the ability to identify known information, ask questions, adequacy of the information needed, skill in creating or compiling mathematical models, being able to find the right solution strategy, and being able to explain and check the correctness of the solution obtained. This research aims to analyze students' mathematical problem-solving abilities in the topic on mixed integer arithmetic operations based on Polya's problem-solving steps. This research uses a qualitative approach with a narrative research type. The research subjects consisted of 32 junior high school students. Data collection was carried out using mathematical problem-solving ability test instruments and interviews with several selected participants. Data was analyzed based on Polya's problem solving steps. Based on the results of data analysis, students' problem-solving abilities obtained based on these four steps are in the form of students who can determine important information in the problem and can plan solutions resulting in them being able to solve problems more regularly, namely by executing the plans they have planned. After that, students who understand the problem well can also check the correctness of the answers they have obtained. Therefore, it is hoped that this research can help teachers to implement a learning process that can develop problem solving abilities.